Analisis pelaksanaan Konstruksi Dalam Pengerjaan (KDP) pada pekerjaan konstruksi Dinas Pekerjaan Umum dan Penataan Ruang Daerah Provinsi Sulawesi Utara - Waridin, Juliani; Ilat, Ventje; Gamaliel, Hendrik (Yayasan Widyantara Nawasena Raharja, 2024)
The aim of this research is to identify, analyze and describe: the implementation of KDP at the North Sulawesi Province PUPRD Service, the obstacles faced in managing KDP at the North Sulawesi Province PUPRD Service, and to describe what efforts have been made to overcome obstacles to KDP management at the Department. PUPRD North Sulawesi Province. This type of research is descriptive research with a qualitative approach. To collect data that is related or relevant to the variables of this research, the techniques used are observation techniques, interview techniques and documentation techniques. The results of the research show that 1) Implementation of Construction in the Work of the Public Works and Regional Spatial Planning Department of North Sulawesi Province which consists of: Mechanism for Procurement of Construction in Work, Recognition of Construction in Work, Measurement of Construction in Work, and Presentation and Disclosure of Construction in Work. 2) obstacles in managing construction in the work of the Public Works and Regional Spatial Planning Department of North Sulawesi Province consisting of policy constraints and leadership commitment, integrity and conflicts of interest 3) Efforts made by the Public Works and Regional Spatial Planning Department of North Sulawesi Province in overcoming obstacles Management of Construction in Progress, namely administrative sanctions, determination of blacklists, coordination and inventory, and payment of remaining debts.